THE MUSLIM EAST IN THE EARLY 21ST CENTURY: CURRENT DEVELOPMENT TRENDS AND PROSPECTS - BELOKRENITSKIY, Viacheslav (CENTRAL ASIA AND THE CAUCASUS, 2005)
Religion and various aspects of its development are still the most urgent issues of our day. This is especially true of Islam, which is frequently regarded as an obstacle on the road to progress. It is commonly accepted that the religion itself, which concentrates on the after world, is mainly indifferent to the ideals of earthly existence and social processes. It is not religion itself but the related culture, primarily political culture, customs, and ideas which give rise to these concerns. In this sense, we can compare these two very different concepts as Islam and development. When discussing Islam we are not referring to religion itself, but rather to the society related to it, and not so much Islamic society in the profound and omniscient meaning of the word, but Islamized, or Muslim society. For the purpose of our comparison let us take politically shaped communities as an example, the majority of which are internationally recognized states. They are described as Muslim either because Muslims comprise the majority of their populations, who acquired the faith themselves or inherited it from their ancestors, or because their titular nations consist of Muslims in the sense described above and claim control over the state’s entire territory or its largest part by force of tradition. What is meant by development? There are three sides to it. The first side is economic, or the production and consumption of commodities and services; improving and widening their range; eliminating hunger and destitution; and bringing down the level of chronic unemployment and poverty. The second, the political side, lies in ensuring security and conditions for the civilized and peaceful life of the people in the absence of conflicts, manifestations of separatism, and stable alienation from power which disrupt the fabric of social life. The third is the sociocultural side, associated with conditions conducive to wider literacy and broader access to education and information sources and technologies, as well as to means of health protection, hygiene, and sanitation.